2020
DOI: 10.1111/cpf.12657
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in the association between PTSD symptoms with cardiac autonomic function and subclinical atherosclerotic risk

Abstract: Although the overall incidence of post-traumatic stress disorder (PTSD) is low in the general population (estimated to be ~12%), PTSD is still a formidable public health concern (Spottswood, Davydow, & Huang, 2017). PTSD increases risk for early-age car

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…According to data from the literature, there are also sex differences in the association of PTSD symptoms and subclinical atherosclerosis. In men, increased PTSD symptoms may increase CVD risk by increasing sympathovagal balance and aortic stiffness [ 27 ]. For certain CVD conditions, particularly hypertension, the associations between wartime stressors and late-life cardiovascular comorbidities diverge across gender by women experiencing higher penalties for their exposure to war-related stressors than their male counterparts [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to data from the literature, there are also sex differences in the association of PTSD symptoms and subclinical atherosclerosis. In men, increased PTSD symptoms may increase CVD risk by increasing sympathovagal balance and aortic stiffness [ 27 ]. For certain CVD conditions, particularly hypertension, the associations between wartime stressors and late-life cardiovascular comorbidities diverge across gender by women experiencing higher penalties for their exposure to war-related stressors than their male counterparts [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…For women, PTSD was associated with metabolic syndrome overall (adjusted OR = 1.53, 95% CI = 1.01–1.95) and the prevalence of the high-density lipoprotein cholesterol component (adjusted OR = 1.98, 95% CI = 1.04–2.12), indicating that the relationship between PTSD and metabolic syndrome may be confined to women. Finally, a small cross-sectional study ( n = 61) found sex differences in the association between subclinical PTSD symptoms and subclinical atherosclerosis in young adults [ 62 ]. In men, PTSD symptom severity was associated with increased aortic stiffness, indicative of vascular damage which may contribute to the increased risk of CVD.…”
Section: Medical and Psychiatric Comorbiditiesmentioning
confidence: 99%